Online Prostitution: Trends of The Commercial Sex Service Industry in Social Media - Christiany Juditha (Jurnal Pekommas, 2021)
The disclosure of various cases of online prostitution in recent years by the police shows that this industry is becoming a trend in online media. Whereas in Indonesia prostitution remains an illegal business and a crime regulated in the KUHP and the ITE Law. The purpose of this study is to obtain an overview of the trends in the commercial sex services industry on social media. The research method is literature study. The results show that the development of e-commerce in general dominates the world market is directly proportional to the development of the commercial sex service industry in online media. The system of selling sex services has changed from conventional systems to modern markets, namely in information, financial and service transactions. Online prostitution information transactions on social media are very open. It can be seen from the services offered, prices, payment methods, rules for using services to customer testimonials. Payment transactions are also more practical and profitable because the process uses a transfer system to the account of the service provider. Although there are still those that impose direct cash payments at the service execution location. Internet technology makes it possible to run a business, promote, increase the income of actors, and reach a wider market. Prospective users can also order services directly through social media/online booking sites without having to go to localization. This is what makes the online sex service industry never die.